(untitled) (The Research of Medical Science Review, 2025)
Malaria was the intended outcome of this investigation of the prevalence of the disease among patients attending two large hospitals in Hyderabad, Sindh, Pakistan. From January 2024 through June 2024, 375 blood samples from patients at two prominent government teaching hospitals the Liaquat University Hospital (also known as Civil Hospital) and the Aga Khan Maternal and Child Care Centre, Hospital of Hyderabad were randomly obtained for the purpose of diagnosing malaria. A thin blood film and a thick blood film were created on a slide in order to identify Plasmodium parasites under a microscope. Plasmodium was found in 66 out of the total samples. Males had a higher prevalence of positive cases (23.5%) than females (10.5%), making up 17.6% of the total. The male age group over 14 years had the highest proportion at 27.5%, while the female age group under 5 years had the lowest frequency at 5%. The urban population had the lowest frequency at 11.3%, while the rural population had the highest at 21.7%. Mixed infections of Plasmodium vivax and Plasmodium falciparum demonstrated the lowest malaria frequency at 0.8%, whereas P. vivax constituted the most frequent malaria infection at 15.5%.